Συγκριτική αξιολόγηση επενδύσεων διαφόρων τεχνολογιών ανανεώσιμων μορφών ενέργειας στην Κύπρο - Βασιλείου, Σέργιος (Τμήμα Μηχανολόγων Μηχανικών και Επιστήμης και Μηχανικής Υλικών, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2013)
This thesis aims to present the renewable energy sources (RES) as well as the ways they are utilised in Cyprus. Environmental protection and energy saving are achieved through RES. Therefore, the development and promotion of such technologies are important investment goals. Cyprus location, can positively contribute to their promotion. Cyprus Government is well aware of the benefits of renewable energy sources and as an EU member state has set out plans within the EU framework to encourage the use of renewable energy investments. These plans are presented in this thesis. Moreover, Cyprus energy strategy as well as the future energy objectives of our country are analysed in detail. The current research objectives which are extensively analyzed are related with the design, research and analysis of the widely used category of RES in our country. This is the production of hot water (DHW) through solar thermal systems and electricity generation through photovoltaic systems. RETscreen software analysis, which is widely used, has been used for the purpose of achieving the research goals. The software in the analysis of these two RES technologies took into consideration all the elements such as climatic data, investment costs and state funding. This led to the illustration of the results and conclusions of this project. The results and conclusions drawn from the analysis indicated the ways for rational use and energy conservation of solar thermal systems. The huge advantage of photovoltaic systems usage is demonstrated. Thus, photovoltaic systems’ investments are encouraged in contrast with 2011 when these systems were not developed. Closing, the research provides a number of recommendations for the improvement and rational use of both RES categories, in order to achieve optimal results.
Keywords: Ανανεώσιμες Πηγές Ενέργειας; Παραγωγή Ζεστού Νερού Χρήσης; Ηλιακά Θερμικά Συστήματα; Φωτοβολταϊκά Συστήματα; Renewable Energy Sources; Production of Hot Water; Solar Thermal Systems; Photovoltaic Systems